Too Much Academic Research Is Being Published - Altbach, Philip G.; de Wit, Hans (International Higher Education, 2018)
There is a crisis in academic publishing and in the global knowledge-distribution system in general—there is too much pressure on top journals, there are too many books and articles of marginal quality, predatory journals are on the rise, and there is a tremendous pressure on academics worldwide to publish. We propose recognizing that most universities and most academics, globally, focus on teaching, and that the large majority of universities acknowledge their important roles as teaching-focused and do not seek to become research-intensive institutions. We call for quality, but also for control of what quality is, by the academic community instead of by nonacademic rankers, publishers, and citation and impact measurers. Quality—not quantity—should be the objective, in combination with an effort to bring quality control back into the academic community—while making sure that that control is not dominated by small groups in research universities in the rich countries.